Studies of Ag/TiO2 plasmonics structures integrated in side polished optical fiber used as humidity sensor - Yusoff, Siti Fatimah Az Zahra; Lim, Chin Seong; Azzuhri, Saaidal Razalli; Ahmad, Harith; Zakaria, Rozalina (Elsevier, 2018)
In this report, we investigate the effects of Ag/TiO2 integrated in side polished optical fiber. Several layers of Ag thickness has been deposited on glass substrates using electron beam (e-beam) evaporation technique in order to determinate the influence of silver with combination of TiO2 on final properties of the sensor. Several thicknesses of Ag NPs were sets to 5 nm, 7 nm, 12 nm, and 16 nm. Another layer of metal oxide, specifically titanium oxide (TiO2) is introduced, covering the Ag layer to study the effect of metal oxides toward the performance of the device. The morphology of the samples was observed using a field-emission scanning electron microscope (FESEM), Raman UV–Vis spectroscopy and Raman photoluminescence (PL) spectroscopy. A CST Microwave used to observe the electric field distribution for all the samples to support the experimental findings. Based on the simulation analysis, two thicknesses of Ag layers (7 nm and 16 nm) were selected to be coated on a side polished optical fiber and tested as a humidity sensor. TiO2 layer was introduced to see the enhancement in the sensing measurements as a suitable material for trapping the photo generated electrons and avoiding charge recombination. From this observation, it can be conclusively shows that the sensitivity of the sensor is improved with integration of Ag NPs and TiO2. Based on the experimental results, the sensor of Ag/TiO2 with 7 nm of Ag layers shows the best characteristics in humidity sensing with good sensitivity and linearity of 0.9201% and 13.4 mW/% RH, respectively.